2000
DOI: 10.1002/(sici)1097-4628(20000516)76:7<1019::aid-app5>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coupling agent and chemical treatment on rice husk ash‐ filled natural rubber composites

Abstract: Rice husk ash was incorporated into natural rubber (NR) using a laboratory size two-roll mill. Curing using a conventional vulcanization system (CV) was chosen, and cure studies were carried out on a Monsanto rheometer. Physical testing of the NR vulcanizates involved the determination of tensile, tear, and abrasion resistances, and hardness. Fourier transform infrared spectroscopy (FTIR) analysis was done to verify the presence of the characteristic functional groups of precipitated silica in MHA (milled husk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…In the same way, Ismail et al [79] also found an increase of the tensile strenght as WRHA increased, until a maximun of 10 phr. This behavior is in accordance with Costa et al [101] which is attributed to the possible particles agglomeration, as commented above.…”
Section: Rha /Elastomers Compositessupporting
confidence: 93%
See 4 more Smart Citations
“…In the same way, Ismail et al [79] also found an increase of the tensile strenght as WRHA increased, until a maximun of 10 phr. This behavior is in accordance with Costa et al [101] which is attributed to the possible particles agglomeration, as commented above.…”
Section: Rha /Elastomers Compositessupporting
confidence: 93%
“…As a result, the composites filled at 20 phr with treated RHA showed a higher tensile strength as compared with the NR filled at 20 phr with commercial silica (Zeol-175), and even higher than the Zeol-175/NR composite compatibilized with Si-69 [101]. In the same way, Ismail et al [79] also found an increase of the tensile strenght as WRHA increased, until a maximun of 10 phr.…”
Section: Rha /Elastomers Compositesmentioning
confidence: 74%
See 3 more Smart Citations